1999
DOI: 10.1093/ageing/28.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of delirium subtypes in older people

Abstract: Objective: to examine the relative frequency and outcome of clinical subtypes of delirium in older hospital patients. Design: prospective observational study. Setting: acute geriatric unit in a teaching hospital. Subjects: 94 patients with delirium from a prospective study of 225 admissions. Measurements: clinical subtypes of delirium were determined according to predefined criteria. Characteristics examined in these subgroups included illness severity on admission, prior cognitive impairment, mortality, durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
1
13

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(172 citation statements)
references
References 21 publications
4
149
1
13
Order By: Relevance
“…In our study, most patients were classified as having a hypoactive symptom profile, confirming the results of previous studies. 1,13,19 In the early postoperative period, more patients had emotional rather than psychotic symptoms. The sensitivity of the CAM in detecting various subtypes of delirium was tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, most patients were classified as having a hypoactive symptom profile, confirming the results of previous studies. 1,13,19 In the early postoperative period, more patients had emotional rather than psychotic symptoms. The sensitivity of the CAM in detecting various subtypes of delirium was tested.…”
Section: Discussionmentioning
confidence: 99%
“…12 Delirium is associated with a disturbance in psychomotor activity, which can be classified into various clinical types, such as hyperactive, hypoactive, and mixed hyperactive and hypoactive. 13,14 Psychotic and emotional signs and symptoms are also common in older patients with delirium. 14,15 Delirium develops rapidly, within a few hours or days, and fluctuates.…”
mentioning
confidence: 99%
“…[22,23] Effective management of modifiable risk factors is an integral component of a successful delirium prevention program.…”
Section: Risk Factorsmentioning
confidence: 99%
“…[5] A study conducted in post-surgical patients found a more pronounced association of long-acting benzodiazepines with delirium compared with shorter-acting benzodiazepines. [23] Moreover, higher doses of benzodiazepine medications during a 24-hour period appear to be associated with an increased risk of delirium compared with lower doses. If benzodiazepines cannot be avoided, a suggestion is to use the lowest dose and shortest acting formulation possible to re-duce the risk of adverse effects such as delirium.…”
Section: Benzodiazepinementioning
confidence: 99%
“…In the past, delirium was considered as a transitory syndrome. Several studies [37][38][39][40] in non-ICU setting have shown that delirium symptoms can persist up to 1 month after the first diagnosis. 41 Pisani et al, 12 analysing the effect of delirium on mortality, reported the persistence of delirium up to 10 days after the first diagnosis in ICU patients.…”
Section: Delirium Terminology and Time Coursementioning
confidence: 99%